ANALISIS PELAKSANAAN PEMBANGUNAN BERKELANJUTAN DI KOTA BATU - Rozikin, M. (Jurnal Review Politik, 2012)
This paper is a study of qualitative approach about sustainable development in the Batu city. The conventional development has managed to increase economic growth, but failed in the social and environmental aspects. The studies show that perception of economic development is economic growth, so that the social and environmental factors are put in a less important position. Development paradigm shift to sustainable development. Indonesia is an agricultural country that has quite large agricultural potential, so that the development of agriculture has to be an important strategy of development. One manifesttation of the development of sustainable agriculture is a policy of agropolitan regional development, which is carried out in Batu city.